Genotype-Driven Pathogenesis of Atrial Fibrillation in Hypertrophic Cardiomyopathy: The Case of Different TNNT2 Mutations - Pioner, Josè Manuel; Vitale, Giulia; Gentile, Francesca; Scellini, Beatrice; Piroddi, Nicoletta; Cerbai, Elisabetta; Olivotto, Iacopo; Tardiff, Jil; Coppini, Raffaele; Tesi, Chiara; Poggesi, Corrado; Ferrantini, Cecilia (Frontiers in Physiology, 2022)
Atrial dilation and atrial fibrillation (AF) are common in HCM patients and associated with a worsening of prognosis. The pathogenesis of atrial myopathy in HCM remains poorly investigated and no specific association with genotype has been identified. By re-analysis of our cohort of thin-filament HCM patients (Coppini et al. 2017) AF was identified in less than 10% of patients with sporadic TNNT2 mutations , while AF occurrence was much higher (25% to 75%) in patients carrying specific “hot-spot” mutations. To determine the molecular basis of arrhythmia occurrence, two HCM mouse models expressing human TNNT2 variants (a “hot-spot” one, R92Q, and a “sporadic” one, E163R) were selected according to the different pathophysiological pathways previously demonstrated in ventricular tissue. Echocardiography studies showed a significant left atrial dilation in both models, but more pronounced in the R92Q. In E163R atrial trabeculae- in line with what previously observed in ventricular preparations- the energy cost of tension generation was markedly increased. However, no changes of twitch amplitude and kinetics were observed, and there was no atrial arrhythmic propensity. R92Q atrial trabeculae, instead, displayed normal ATP consumption but markedly increased myofilament calcium sensitivity, as previously observed in ventricular preparations. This was associated with reduced amplitude and slower kinetics of twitch contractions and, importantly, with an increased occurrence of spontaneous beats and triggered contractions that represent an intrinsic arrhythmogenic mechanism promoting AF. The association of specific TNNT2 mutations with AF occurrence depends on the mutation-driven pathomechanism (i.e. increased atrial myofilament calcium sensitivity rather than increased myofilament tension cost) and may influence the individual response to treatment.